2015
DOI: 10.3390/ijerph121215034
|View full text |Cite
|
Sign up to set email alerts
|

Time Perspective and Emotion Regulation as Predictors of Age-Related Subjective Passage of Time

Abstract: Hardly any empirical work exists concerning the relationship between the intra-individually stable time perspective relating to the past, present, and future and the subjective speed of time passing in everyday life. Moreover, studies consistently show that the subjective passage of time over the period of the last ten years speeds up as we get older. Modulating variables influencing this phenomenon are still unknown. To investigate these two unresolved issues, we conducted an online survey with n = 423 partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 57 publications
(85 reference statements)
2
39
0
3
Order By: Relevance
“…In fact, Watkins (2014) maintains that grateful people, who are more focused on pleasant events, tend to be more attentive to what they currently have. This is related to research showing that a more pronounced present perspective at the expense of the future perspective is linked to lower ability to delay gratification (Wittmann, Rudolph, Linares Gutierrez, & Winkler, 2015). Furthermore, individuals with a hedonistic orientation toward the present perceive their life as more purposeful (Sobol-Kwapiñska & Jankowski, 2016).…”
Section: Discussionmentioning
confidence: 92%
“…In fact, Watkins (2014) maintains that grateful people, who are more focused on pleasant events, tend to be more attentive to what they currently have. This is related to research showing that a more pronounced present perspective at the expense of the future perspective is linked to lower ability to delay gratification (Wittmann, Rudolph, Linares Gutierrez, & Winkler, 2015). Furthermore, individuals with a hedonistic orientation toward the present perceive their life as more purposeful (Sobol-Kwapiñska & Jankowski, 2016).…”
Section: Discussionmentioning
confidence: 92%
“…Future was correlated with BActing with Awareness^and Binsight^(r = .36 and .42), which is interesting given the lack of association of Future and global mindfulness in Drake et al (2008). Similarly, Wittmann et al (2015a) reported a moderate positive association between FMI Bpresence^(the only mindfulness score included) and Present Hedonistic (but cf. Wittmann et al 2014), a scale that was either unrelated to mindfulness or even negatively associated with mindfulness in other studies (e.g., Drake et al 2008;Seema and Sircova 2013).…”
mentioning
confidence: 80%
“…While performing a demanding cognitive task, they experience higher task engagement, lower worry, and less distress, which in turn, results in higher levels of performance . They also feel time in a different way, experiencing slower passage of time, lower time pressure, lower boredom, and less routine (Wittmann et al, 2015). They remain more satisfied with their romantic relationships (Stolarski, Wojtkowska, & Kwiecińska, 2016), make more healthy leisure choices (Garcia & Ruiz, 2015) and are more ethical in their business dealings (Unger, Yan, & Busch, in press).…”
Section: The Ideal Temporal Profile: Balanced Tpmentioning
confidence: 99%